Lamellar silver thiolate coordination polymers with reversibly switchable blue-to-near infrared optical transitions. Issue 34 (23rd July 2021) - Wang, Junren; Graf, Robert; Riedinger, Andreas
Abstract : Lamellar silver thiolates (Ag-MPA) possess reversible temperature dependent blue-to-near infrared optical transitions resulting from metallophilic interactions in the layers and conformational stabilization of the ligands. Abstract : We discovered that lamellar silver thiolates (Ag-MPA) possess reversible temperature dependent blue-to-near infrared optical transitions. Our analyses revealed that structural flexibility of Ag-MPA is responsible for the transitions. The polymer-like nature of Ag-MPA makes up-scaling the reaction feasible and allows for facile processing for applications ranging from bio-imaging to opto-electronics.